Dinamika Sengketa Pemilihan Raja dalam Masyarakat Adat: Analisis Politik Hukum dan Maslahah di Negeri Haruru - Muhammad Zun Nun Tuhepaly; Ratno Lukito (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
The dispute over the election of the Raja (traditional king) in Haruru Village, Central Maluku Regency, is not merely related to competing genealogical claims among matarumah (customary lineage groups), but also involves legal, political, and indigenous governance dimensions. This study aims to analyze the dispute resolution mechanism of the Raja election based on customary law and applicable regulations, as well as to evaluate its resolution from the perspective of maslahah (public interest). The study employed a qualitative approach using empirical legal research combined with normative analysis. Data were collected through in-depth interviews, document analysis, and literature review, and were analyzed using the interactive model of Miles, Huberman, and Saldaña through the lenses of legal politics and maslahah. The findings reveal that the dispute is influenced by regulatory ambiguities, weak genealogical verification mechanisms, broad institutional discretion, and the complexity of legal pluralism involving customary law, regional regulations, and state law. From the perspective of maslahah, dispute resolution should be directed toward achieving collective welfare through the establishment of an independent genealogical verification body, the standardization of Raja election procedures, the strengthening of customary deliberation mechanisms, and the enhancement of transparency and accountability within customary institutions. The study concludes that sustainable resolution of indigenous leadership disputes requires the integration of regulatory reform, harmonization of legal systems, strengthening of customary institutions, and a public-interest-oriented approach to promote justice, legal certainty, and social stability within indigenous communities.